Evolution of the Canterbury Dedicated Education Unit model. (July 2020) - Borren, Joanne; Harding, Thomas
Abstract: The Dedicated Education Unit (DEU) model of clinical teaching and learning represents a substantial shift in philosophy from the previous preceptorship model in undergraduate nursing education in Canterbury, New Zealand. This research aims to identify the factors underpinning the evolution of the Canterbury DEU model. It utilised a qualitative case study design with inductive and deductive thematic analysis of archival documents and three key informant interviews. Analysis identified centrality of relationships and a progressive culture shift as integral to the development of the Canterbury DEU. The relationships vital to the success of the DEU model are evidenced at varying organisational levels between the health care and education provider and have been essential to the substantive growth of the DEU model in Canterbury, from an initial five pilot sites in 2007 to 47 DEUs in 2017. Highlights: Substantial growth in the number of Dedicated Education Units in Canterbury, New Zealand. Relationships between the healthcare and education provider were fundamental to the development of the Canterbury DEU model. Canterbury Dedicated Education Unit model promotes the value of nursing students to clinical areas. Findings could assist nursing education providers interested in establishing Dedicated Education Units.